2022
DOI: 10.1002/chem.202200996
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Mesityl Azide with Ferrocene‐Based N‐Heterocyclic Germylenes, Stannylenes and Plumbylenes, Including PPh2‐Functionalised Congeners

Abstract: The reactivity of ferrocene-based N-heterocyclic tetrylenes [{Fe(η 5 À C 5 H 4 À NSitBuMe 2 ) 2 }E] (E = Ge, Sn, Pb) towards mesityl azide (MesN 3 ) is compared with that of PPh 2functionalised congeners exhibiting two possible reaction sites, namely the E II and P III atom. For E = Ge and Sn the reaction occurs at the E II atom, leading to the formation of N 2 and an E IV =NMes unit. The germanimines are sufficiently stable for isolation. The stannanimines furnish follow-up products, either by [2 + 3] cycload… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 159 publications
1
9
0
Order By: Relevance
“…In 2022, Siemeling et al reported the reactions of ferrocene-based N-heterocyclic plumbylene with azides (Scheme 110). 153 The plumbylene Pb3 did not react with MesN 3 even heating the toluene solution at 105 °C. In contrast to Pb3 , the PPh 2 -functionalised congener Pb4 smoothly reacted with MesN 3 at 60 °C to generate the additional product Pb4-P in 52% yield.…”
Section: Reactions Of Main Group Compounds With Azidesmentioning
confidence: 98%
See 2 more Smart Citations
“…In 2022, Siemeling et al reported the reactions of ferrocene-based N-heterocyclic plumbylene with azides (Scheme 110). 153 The plumbylene Pb3 did not react with MesN 3 even heating the toluene solution at 105 °C. In contrast to Pb3 , the PPh 2 -functionalised congener Pb4 smoothly reacted with MesN 3 at 60 °C to generate the additional product Pb4-P in 52% yield.…”
Section: Reactions Of Main Group Compounds With Azidesmentioning
confidence: 98%
“…In 2022, Siemeling et al developed the ferrocene-based N-heterocyclic germylenes and investigated their reactivity towards azides (Scheme 89). 153 Treatment of Ge14a with MesN 3 in hexane led to the formation of germanimine Ge14a-P in 72% yield. Ge14b with a PPh 2 functionality reacted with MesN 3 affording the germanimine Ge14b-P1 in 72% yield.…”
Section: Reactions Of Main Group Compounds With Azidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ge–N bond distance is 1.647(4) Å, which is the shortest among the reported GeN double bonds (1.67–1.72 Å). 17–25 It is even shorter than that in the carbene stabilized cationic germanimine (1.669(4) Å) reported by Aldridge and coworkers. 20 The distances of Ge1–Cl1 (2.2043(12) Å) and Ge1–C1 (1.931(4) Å) are both slightly shorter than those found in the precursor M s Fluind t Bu -GeCl (Ge–Cl: 2.2500(6) Å; Ge–C: 2.007(2) Å).…”
mentioning
confidence: 71%
“…16 Since then, several stable germanimines have been obtained by employing sterically congested ligands to thermodynamically and kinetically stabilize the reactive GeQN double bonds. [17][18][19][20][21][22][23][24][25] Strikingly, Ando et al synthesized bisgermanimines II through the reactions of bis[bis(trimethylsilyl)methyl]germylene with diazidosilanes. 18 The Fulton group obtained a series of germanimines, which were synthesized by the reactions of diaminogermylenes and organic azides.…”
mentioning
confidence: 99%